Bioengineering Technologies for Cardiac Regenerative Medicine - Chingale, Mira; Zhu, Dashuai; Cheng, Ke; Huang, Ke (Frontiers in Bioengineering and Biotechnology, 2021)
Cardiac regenerative medicine faces big challenges such as a lack of adult cardiac stem cells, low turnover of mature cardiomyocytes, and difficulty in therapeutic delivery to the injured heart. The interaction of bioengineering and cardiac regenerative medicine offers innovative solutions to this field. For example, cell reprogramming technology has been applied by both direct and indirect routes to generate patient-specific cardiomyocytes. Various viral and non-viral vectors have been utilized for gene editing to intervene gene expression patterns during the cardiac remodeling process. Cell-derived protein factors, exosomes, and miRNAs have been isolated and delivered through engineered particles to overcome many innate limitations of live cell therapy. Protein decoration, antibody modification, and platelet membranes have been used for targeting and precision medicine. Cardiac patches have been used for transferring therapeutics with better retention and integration. Other technologies such as 3D printing and 3D culture have been used to create replaceable cardiac tissue. In this review, we discuss recent advancements in bioengineering and biotechnologies for cardiac regenerative medicine.